RESPON DAN MINAT PETANI TERHADAP PENGGUNAAN ALAT CUCI LADA DI DESA PETALING BANJAR KECAMATAN MENDO BARAT KABUPATEN BANGKA - Herpiyandi, Herpiyandi; Evahelda, Evahelda; Yulia, Yulia (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
This study aims to describe the response of farmers to the washing tools for pepper in the village of Petaling Banjar, Mendo Barat disrict, Bangka regency and to analyze the factors that influence the interest of farmers using pepper equipment in the village of Petaling Banjar, Mendo Barat district, Bangka regency. Time and place of this research was carried out from July 2020 to December 2020 in the village of Petaling Banjar, Mendo Barat district, Bangka regency. The research method used is a survey method. The sampling method used was quantitative descriptive with a likert scale and binary logistic regression. The results showed that the response of farmers to the use of pepper washing tools in the village of Petaling Banjar, Mendo Barat district, Bangka regency was categorized as good with a percentage of 74,2%. Cognitif response, namely the level of understanding and knowledge of the respondent farmers on pepper washing tools was 74,2%, a good response. Affective response, namely attitudes, assessments, and farmers interest in washing pepper was 74,2%, a good response. Conative response, namely the behavior or actions that have been taken by farmers to washing pepper tools, 38% of which responded well and 51,71% responded well enough. The factors that influence farmers interest in using pepper washing equipment in the petaling banjar village, Mendo Barat district are the amount of production, the perception of washing time, the perception of the level of ease of tools, and the perception of the quality of the results.